Exploring Methodological Inventiveness Through Collective Artful Self-Study Research (LEARNing Landscapes, 2016)
We are teacher educators working in South Africa and the United States. Collectively we explored and extended our understanding of methodological inventiveness in self- study research through an artful process we have named "virtual polyvocal research jamming." We make explicit our extemporary, dialogic process, showing how we imagined and played with artful research practices: rich pictures, poetry, oral performance, and dance. Through collective analysis of our process and products, we share our learning about methodological inventiveness, highlighting how nding imaginative ways to express and make sense of insights can deepen and extend shared re ection, analysis, and communication in educational inquiry.
Keywords: teacher education; self-study; methodological inventiveness; artful research; dance; performance; poetry; rich picture